Strategies to Improve the Performance of District Employees in Achieving Good Governance - Dian Wahyu Danial; Jaka Permana; Rapiudin Rapiudin (HK-Publishing, 2024)
Abstract Employee performance at the sub-district level serves as the spearhead of public service and determines the successful implementation of good governance. This study aims to analyze strategies for improving employee performance at the Cikeusik Sub-district Office, Pandeglang Regency, and to identify obstacles to achieving good governance. A descriptive qualitative research method was employed. Data were collected through in-depth interviews with key informants including the Sub-district Head, Sub-district Secretary, Section Heads, and operational staff and supplemented by direct observation and document analysis. Data analysis utilized the interactive model developed by Miles and Huberman, comprising data reduction, data display, and conclusion drawing. The results indicate that performance improvement strategies were implemented through close supervision of employee discipline, monthly performance evaluations, the restructuring of job assignments (job placement), peer-to-peer technical guidance, and the digitalization of population administration services. However, the implementation of these strategies remains hindered by structural factors, such as limitations in the quantity and quality of human resources, low digital literacy among senior staff, constrained operational budgets, and unstable internet network infrastructure in outlying areas. Therefore, support from the regency government is required specifically increasing the quota of competent personnel and upgrading information technology equipment—to uphold the principles of accountability, transparency, and service responsiveness in Cikeusik Sub-district. Keywords: Strategy, Employee Performance, Good Governance.